The Effect of Audit Committee Financial Expertise And Relative Status On Earnings Management: Case of Indonesia - Sylvia Veronica Siregar, Delfita Siagian, (Jurnal Akuntansi, 2018)
Ã‚Â The aim of this research is to examine the effect of audit committee financial expertise (measured by audit committee experience in accounting, supervision, and financial)and audit committee status (relative to management) on earnings management. Our samples consist of 384 observations in Indonesia Stock Exchange for the year 2012-2014. The result of this research shows that audit commite financial expertise has no significant effect on earnings management. However, we find evidence that audit committee financial expertise haspositive effect on income decreasing accruals. This finding indicates that audit committee may perceived that conservatism is one of the mechanism to restrict management opportunistic behavior. We do not find significant evidence of the joint effect of audit committee status and audit committeee expertise on earnings management.